Alterations in whole-brain white matter fiber networks in individuals with autism spectrum disorder after social skills training - Gang-Qiang Han; Siu-Ching Kat; Hui Wang; Yu-Lu Yang; Zeng-Hui Ma; Ting-Ni Yin; Ya-Jing Sun; Xin-Zhou Tang; Xiao-Yun Gong; Duo Wang; Lei Li; Bing-Xi Sun; et al. (Brain Research Bulletin, 2025)
Social skills training (SST) has demonstrated efficacy in improving social deficits in individuals with autism spectrum disorder (ASD), but the underlying neural mechanisms remain unclear. This study investigated alterations in whole-brain white matter network topology after SST in ASD individuals and explored potential correlation with improvements in social interaction deficits. 38 ASD patients aged 12 - 30 years were recruited, including 19 who completed magnetic resonance imaging (MRI) scans and social responsiveness scale (SRS) assessments at both baseline and the endpoint of a 14-week SST (training group) and 19 age-, sex-, and IQ-matched patients who underwent MRI scans and SRS assessment at the same time points but did not receive SST (control group). White matter connectivity matrices were constructed using diffusion tensor imaging (DTI), and graph theory analysis was used to assess global and nodal network properties. Paired t-tests and independent-samples t-tests were used for within- and between-group comparisons, respectively. Pearson's partial correlation was used to examine associations between network changes and SRS scores changes. After SST, four edges showed significant changes in white matter connectivity (FDR-corrected), with three increased and one decreased in the training group. Changes in nodal betweenness were also observed. While SRS scores significantly decreased in the training group, no significant correlations were found between neuroimaging changes and behavioral improvements, possibly due to the limited sample size. These findings suggest that SST may reshape white matter network, offering insights into its neural mechanisms and informing novel ASD intervention strategies.